Decomposition of sorghum, grass, and sorghum intercropped with grass and soybean performance in integrated systems in the Cerrado - Joilson Sodré Filho; Arminda Moreira de Carvalho; Robélio Leandro Marchão; Ricardo Carmona (Scientia Agricola, 2024)
ABSTRACT Previous cultivation of sorghum (Sorghum bicolor), Congo grass (Urochloa ruziziensis), and palisade grass (Urochloa brizantha cv. ‘Marandu’) may influence soybean (Glycine max) agronomic performance. The present work evaluated the decomposition of sorghum, grass, and sorghum intercropped with grass in the off-season to improve soybean yield in integrated crop systems in the Brazilian Cerrado and their dry matter production. This study was conducted in Planaltina, DF, in Central-West Brazil, on a Typical Acrustox soil from Mar 2010 until Feb 2012. The experimental design was a randomized block, with six crop systems before soybean: fallowing, sorghum, palisade grass (alone or intercropped with sorghum), and Congo grass (alone or intercropped with sorghum) with four replicates. Soybean agronomic performance, the crop systems’ dry mass, and its decomposition rate were estimated over two years. Higher soybean grain yields were observed in cropping systems including Congo grass alone (3,349 kg ha–1) or intercropped with sorghum (3,317 kg ha–1). Sorghum intercropped with palisade grass produced 18,702 kg ha–1 of dry matter and 64.9 % (on average) of soil coverage during the soybean cycle. However, the highest lignin content was observed in sorghum intercropped with Congo grass (5.1 % on average). The results indicate that the cultivation of Congo grass, either alone or intercropped with sorghum, improves the agronomic performance of soybean in succession, compared to sorghum alone or palisade grass (alone or intercropped with sorghum). The intercropped systems provided the best nutrient efficiency use aiming at sustainable agriculture in the Cerrado region.